Difficult passages in the New Testament interpreation puzzling texts in the Gospels and Epistles - Stein, Robert H. 1935- (Grand Rapids, MI Baker, 1990)
Includes bibliographical references and index.
A compilation of three previously published works: Difficult passages in the Gospels (1984), Difficult sayings in the Gospels (1985), and Difficult passages in the Epistles (1988).
Keywords: Bible. N.T. -- criticism, interpretation, etc; Jesus Christ -- teachings